EFFECT OF DRUM DRYER NOZZLE DESIGN ON HYDRODYNAMIC REGIMES - N. Rajabova; A. B. Qodirov (Web of Journals Publishing, 2023)
The article examines the process of drying by pickling and the analysis of the devices used in it, the existing problems in the process and their optimal solutions, as well as the hydrodynamic regimes of the drum dryer. The equation that determines the total hydraulic resistance of the device and the resistance coefficient of the contact element is recommended.
Keywords: convective, drum dryer, nozzle, contact element, hydraulic resistance, hydrodynamic regime, contact surface.